Design and Performance Analysis of WiFi Microstrip Patch Antenna under Different Bending Conditions using Flexible Substrates - Prabhu, Sadhish S.; Tharini, C.; Aslam, Mohamed N. M. (Engineering, Technology & Applied Science Research, 2024)
Textile-based antennas are of great importance for wearable devices due to their flexible and compact design, which allows the creation of efficient wearable technologies. However, the use of flexible substrates in wearable antennas presents a number of challenges, including frequency shifts that occur during bending. A comprehensive analysis of the bending characteristics of flexible substrates is absent from the existing literature. The objective of this study is to analyze the performance of a Wi-Fi Microstrip Patch Antenna (MPA) designed to operate at 2.4 GHz using flexible substrates, such as leather, fleece, and felt, with a detailed examination of their bending characteristics. A bending analysis was conducted to measure the impact on performance metrics, such as return loss, bandwidth, gain, and Voltage Standing Wave Ratio (VSWR) under bending angles from 0° to 17°. The leather substrate exhibited minimal degradation in performance. The antenna demonstrated a return loss below -15 dB, a bandwidth exceeding 4%, a gain exceeding 5 dB, and a VSWR lower than 2.5 across all tested conditions. The leather substrate has emerged as a promising candidate for wearable Wi-Fi applications due to its ability to maintain stable performance metrics under bending conditions.